Transformation of Science Literacy in Elementary Schools: Guided Inquiry Learning Model-Based Teacher Training with PhET Simulation in Pringsewu Regency Elementary School - Efendi, Ujang; Pangestu, Deviyanti; Nurwahidin, Muhammad; Pramudiyanti, Pramudiyanti; Saputri, Farida Julia; Oktavian, Wiranto; Pratama, Farhan Iqbal (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
The purpose of carrying out this community service activity is to provide understanding and train stakeholders in implementing technology-integrated learning in elementary schools in Pringsewu Regency. The specific target to be achieved is that participants can implement the PhET Simulations-based guided inquiry learning model in their respective classes so that they can improve students' science literacy. The methods used to achieve the goals and targets are (1) expository: presenting and conveying information about 21st century learning, learning models and media; (2) tutorials and mentoring: providing procedures for implementing the integrated guided inqury model learning of PhET Simulations; (3) assignments and discussions: designing group learning; (4) role playing: implementation of guided inquiry learning integrated with PhET Simulations through teaching practice; (5) carry out pretest and posttest; and (6) reflection and evaluation: discussion of challenges and solutions faced during teaching practice. The target of the activity was teachers and principals of elementary schools in Gadingrejo District, Pringsewu Regency. The expected result is that teachers are able to carry out guided inquiry learning integrated with PhET Simulations to improve students' science literacy. The results obtained from this service activity are an increase in teachers' understanding of 21st century learning, the importance of science literacy is reminded from an early age in elementary schools in Gadingrejo District, Pringsewu Regency. In addition, participants were able to implement the PhET Simulations integrated guided inquiry learning model well through classroom learning and reflect and evaluate the course of learning related to the challenges faced and the solution efforts.